The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12943-018-0786-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel targeted therapies and immunotherapy for advanced thyroid cancers

Abstract: Thyroid cancer is a frequently encountered endocrine malignancy. Despite the favorable prognosis of this disease, 15–20% of differentiated thyroid cancer (DTC) cases and most anaplastic types, remain resistant to standard treatment options, including radioactive iodine (RAI). In addition, around 30% of medullary thyroid cancer (MTC) cases show resistance after surgery. The evolving understanding of disease-specific molecular therapeutic targets has led to the approval of two targeted therapies (Sorafenib and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
180
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(186 citation statements)
references
References 151 publications
1
180
0
5
Order By: Relevance
“…In the last few years, immunotherapy has transitioned from a promising to a well-established option as an oncological treatment for several types of malignancies, acting as an immune checkpoint inhibitor (Emens et al 2017). Preclinical studies on MTC have revealed potential new treatments through the use of immunotherapy (Naoum et al 2018). Several ongoing trials are investigating this type of therapy, including a phase II trial studying a therapy directed toward cells presenting CEA (GI-6207), a therapy focused on programmed death ligand 1 (PDL1) with the use of pembrolizumab (Arasanz et al 2017).…”
Section: Immunotherapymentioning
confidence: 99%
“…In the last few years, immunotherapy has transitioned from a promising to a well-established option as an oncological treatment for several types of malignancies, acting as an immune checkpoint inhibitor (Emens et al 2017). Preclinical studies on MTC have revealed potential new treatments through the use of immunotherapy (Naoum et al 2018). Several ongoing trials are investigating this type of therapy, including a phase II trial studying a therapy directed toward cells presenting CEA (GI-6207), a therapy focused on programmed death ligand 1 (PDL1) with the use of pembrolizumab (Arasanz et al 2017).…”
Section: Immunotherapymentioning
confidence: 99%
“…The dismal prognosis of this rare thyroid malignancy has led to substantial efforts to find the genetic drivers in hopes of developing targeted therapy to improve survival . Previous studies have identified a variety of potential genetic driver events in many ATCs, but a clear understanding of the molecular pathogenesis remains far from complete.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of cancer, MAPK and PI3K signaling pathways are parts of the most successfully studied pathways [39]. These pathways include various gene alterations (mutation, amplification, and deletion) that may contribute to the carcinogenesis and that this may be targeted for therapies.…”
Section: Targeting Mapk and Pi3k Signaling Pathways In Thyroid Cancermentioning
confidence: 99%
“…PTEN is known to antagonize the PI3K/AKT pathway and its loss stimulates this pathway. Around 12% of ATC exhibit mutated or deleted PTEN genes leading to an overactivation of the PI3K/AKT pathway and a more aggressive tumor [39].…”
Section: Targeting Mapk and Pi3k Signaling Pathways In Thyroid Cancermentioning
confidence: 99%
See 1 more Smart Citation